2008
DOI: 10.1007/s12185-008-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C viruses in patients with lymphoproliferative disorders

Abstract: The etiology of most lymphoproliferative disorders remains unclear, though several hypotheses have been proposed. One of the conjectured mechanisms is infection of a tumor clone by an oncologic virus. Recently, evidence has arisen implicating both hepatitis B and, even more so, hepatitis C viruses in the pathogenesis of lymphoproliferative disease. Based on this information, we surveyed the prevalence of hepatitis B and C virus in patients with lymphoproliferative disease. A total of 334 newly-diagnosed lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…1 Epidemiological studies have demonstrated an increased risk of B-NHL among those with persistent HBV and B-NHL. [2][3][4][5] However, the roles of exposure per se, occult infection, antibody response and viral clearance remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Epidemiological studies have demonstrated an increased risk of B-NHL among those with persistent HBV and B-NHL. [2][3][4][5] However, the roles of exposure per se, occult infection, antibody response and viral clearance remain unclear.…”
mentioning
confidence: 99%
“…Geffen Kleinstern, 1 Rania Abu Seir, 2,3 Riki Perlman, 2 Ziad Abdeen, 4 Areej Khatib, 5 Husein Elyan, 6 Eldad J. Dann, 7 Meirav Kedmi, 8 Martin Ellis, 9 Arnon Nagler, 8 Gail Amir, 10 Dina Ben Yehuda, 2 Rifaat Safadi 11 and Ora Paltiel …”
mentioning
confidence: 99%
“…HBV reactivation may be observed in patients during treatment with rituximab (46); however, no conclusive evidence of an association between NHL and hepatitis virus infection has been reported (47). Two studies showed that HBV infection was associated with an increased risk of DLBCL in Korean populations (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…In a few countries, like France, and USA, there are data regarding positive and negative association from different studies [12].Whereas a high prevalence of HCV infection in NHL patients has been shown to exist in many geographical areas of high HCV prevalence such as Brazil [12], Italy [13,14], Israel [15], Yemen [16], Spain [17], Canada [18], Egypt [19], and parts of the USA [12,20]. Many other areas studies have not established any form of association as in Greece [6], Mexico [11], France [12], the UK [21], Thailand [22], The Netherlands [23], Turkey [24,25], and Korea [26]. However, a study in Denmark [27], which is an area of low HCV prevalence, has shown association of HCV and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Okan et al [24], the seropositivity of HBsAg and/or anti-HCV was 8.7% (29/334), and among the controls 6.1% (49/802), however this difference did not achieve statistical significance [OR 1.36; 95% CI (0.82-2.26)]. Thus, they could not find any significant differences between the seropositivity rates of hepatitis B, C, or both in either NHL or Hodgkin's lymphoma and those of population-based controls.…”
Section: Discussionmentioning
confidence: 99%